Adult granulosa tumor of the ovary about a case - Diakhate, Abdoulaye; Niass, Ami; Gning, Gory; Ndiaye, Mame Diarra; Moreira, Philippe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Granulosa tumors are rare tumors of the ovary (0.6 to 3%). They belong to the group of mesenchymal and sex cord tumors, and represent more than 70% of malignant tumors in this group and 5% of ovarian cancers. They present two histological forms: the juvenile form and the adult form, the most common, occurring mainly in women in the post-menopausal period. The solido-cystic appearance of these tumors is generally non-specific and the histological diagnosis can be confirmed by immunohistochemistry. Surgery remains the basis of treatment and must be extensive in elderly patients. The prognosis depends on the histological type and several parameters. We report the observation of a 53-year-old patient without known risk factors, who presented with a granulosa tumor of the left ovary diagnosed postoperatively. The epidemiological, clinical and therapeutic aspects are discussed.